La Contribution Des Etablissements De Microfinance A L2019;inclusion Financiere En Zone CEMAC (Global Journal of Management and Business Research, 2019)
This work aims to assess the effects of financial inclusion on economic growth in the CEMAC zone The approach used for financial inclusion is that of microfinance which is defined as an activity carried out by approved entities that do not have the status of a bank or financial institution The study period extends from 2007 to 2016 the software used for data analysis is EVIEWS it is accompanied by two econometric tests namely the VAR model which establishes the causal link and the Granger causality from which twodimensional causality results The results of this empirical study show that the level of savings the volume of credit the number of agencies and the population have a positive and significant influence on financial inclusion Monetary authorities must therefore contribute to improving financial inclusion in particular by promoting citizen s financial education setting up a platform for financial support system Tracking progress in terms of financial inclusion and tools for promoting financial inclusion in CEMAC zone
Keywords: contribution; microfinance; financial inclusion; CEMAC